2009
DOI: 10.1590/s1413-70542009000100036
|View full text |Cite
|
Sign up to set email alerts
|

Análise Bayesiana no estudo do tempo de retorno das precipitações pluviais máximas em Jaboticabal (SP)

Abstract: RESUMODados históricos de precipitação máxima são utilizados para realizar previsões de chuvas extremas, cujo conhecimento é de grande importância na elaboração de projetos agrícolas e de engenharia hidráulica. A distribuição generalizada de valores extremos (GEV) tem sido aplicada com freqüência nesses tipos de estudos, porém, algumas dificuldades na obtenção de estimativas confiáveis sobre alguma medida dos dados têm ocorrido devido ao fato de que, na maioria das situações, tem-se uma quantidade escassa de d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
2
1
0
4
Order By: Relevance
“…Franco et al (2014) reported that the GEV multiparameter distribution, with its parameters estimated employing the L-moments method, was more suitable for studies of annual maximum daily rainfall in the Rio Verde basin, in the south of Minas Gerais. This result corroborates the findings obtained in other studies in Brazil, such as in Beijo et al (2009), Beskow et al (2015) and Blain e Meschiatti (2014). Despite the scarcity of studies evaluating the applicability of K-4P distribution in Brazil, it is worthwhile to mention the researches developed by Blain e Meschiatti (2014), who achieved satisfactory results in the study of intense rainfall in the city of Campinas-SP, and by Beskow et al (2015) who also found promising results for the modeling of maximum annual daily rainfall.…”
Section: Resultssupporting
confidence: 93%
“…Franco et al (2014) reported that the GEV multiparameter distribution, with its parameters estimated employing the L-moments method, was more suitable for studies of annual maximum daily rainfall in the Rio Verde basin, in the south of Minas Gerais. This result corroborates the findings obtained in other studies in Brazil, such as in Beijo et al (2009), Beskow et al (2015) and Blain e Meschiatti (2014). Despite the scarcity of studies evaluating the applicability of K-4P distribution in Brazil, it is worthwhile to mention the researches developed by Blain e Meschiatti (2014), who achieved satisfactory results in the study of intense rainfall in the city of Campinas-SP, and by Beskow et al (2015) who also found promising results for the modeling of maximum annual daily rainfall.…”
Section: Resultssupporting
confidence: 93%
“…The only method that enabled us to identify adequacy for all stations was the LM associated to the GEV distribution. Similar results were obtained by Beijo;Vivanco andMuniz (2009), Blain (2011) andQuadros;Queiroz and Vilas Boas (2011), proving the great performance of this PDF for maximum daily rainfall. However, these results are different from those obtained by Blain and Camargo (2012), pointing to the GEV -ML with better performance.…”
supporting
confidence: 84%
“…Santos et al (2009) A distribuição Gama, estimada pelo método MV para precipitação mensal no Sudoeste da Bahia, obteve bom ajuste em duas série históricas, segundo o teste de KS por Murta et al (2005). Beijo et al (2009) observaram bom ajuste da distribuição GEV estimada pelo método da MV aplicada em eventos de precipitação máxima na região de Jaboticabal, SP.…”
unclassified